2006
DOI: 10.1175/jam2313.1
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Jets over the Mid-Atlantic States: Warm-Season Climatology and a Case Study

Abstract: Although considerable research has been conducted to study the characteristics of the low-level jets (LLJs) over the Great Plains states, little is known about the development of LLJs over the Mid-Atlantic states. In this study, the Mid-Atlantic LLJ and its associated characteristics during the warm seasons of 2001 and 2002 are documented with both the wind profiler data and the daily real-time model forecast products. A case study with three model sensitivity simulations is performed to gain insight into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 38 publications
5
52
0
Order By: Relevance
“…The core is tightly packed at 25°N, likely, because of steep topography to the west. Topography is known to impact the jet structure from generation of shallow baroclinicity on its slopes (e.g., Zhang et al 2006). At 30°N, the core has shifted to the west and exhibits a more gradual eastward-downward slope, reflecting the underlying terrain slope and related thermal attributes.…”
Section: Thesis Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The core is tightly packed at 25°N, likely, because of steep topography to the west. Topography is known to impact the jet structure from generation of shallow baroclinicity on its slopes (e.g., Zhang et al 2006). At 30°N, the core has shifted to the west and exhibits a more gradual eastward-downward slope, reflecting the underlying terrain slope and related thermal attributes.…”
Section: Thesis Organizationmentioning
confidence: 99%
“…The wet (dry) eastern (western) southern Plains region may produce a local enhancement of the east (high) to west (low) low-level pressure gradient, and thus the GPLLJ (Bosilovich and Sun 1999). An evaporation-LLJ relationship has also been advanced based on boundary layer forcing of the nocturnal jet and its modulation by the diurnally varying radiative responses of dry soil (Zhang et al 2006;Zhong et al 1996) 12 . However the modeling analysis of Giorgi et al found that evaporation and soil moisture forcing was a minor contributor to the drought of 1988 and had it been dominant would have provided a negative feedback to the drought via enhanced dynamical forcing of the low-level circulation (i.e., the GPLLJ).…”
Section: Pentad Resolution Hydroclimatementioning
confidence: 99%
“…Terrain-associated baroclinicity likely also affects low-level jets in other areas of the world (e.g. Saulo et al, 2004;Zhang et al, 2006;Cuxart and Jiménez, 2007), as does baroclinicity associated with land/sea temperature contrasts (e.g. Zemba and Friehe, 1987;Karipot et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fuhrman et al 2008, Brun andBarros 2013). Although weaker than the Low Level JET (LLJ) in the Central Plains (Anderson and Arritt, 2001), it is possible that the nocturnal LLJ east of the Appalachians play an important role on the diurnal cycle of rainfall on analysis of profile observations in the Mid-Atlantic states (Zhang et al 2006). However, current evidence from the existing relatively sparse network of observations is lacking.…”
Section: Science Contextmentioning
confidence: 99%